Design and Development of Automatic Intelligent Locking System with Real Time SMS Notifications - Dogra, Sudip; Sen, Subhadeep; Langal, Kamalendu (International Journal of Computer Sciences and Engineering, 2025)
In the present era security is a great concern for everybody; starting from individuals to banks to any business or government organizations. A GSM Based Security System can serve to address this issue of security to a large extent. This would ensure that unauthorized access to secured areas or information is prevented. Keeping this thought in mind we embarked upon this project of GSM Based Security System using Microcontroller systems. We have intended to develop a system which will work in every infrastructural condition. It will provide access upon correct password only. In case of any unauthorized person tries to enter by putting wrong password the developed system alerts through SMS to predefined mobile numbers.